Competency Standards for Law Enforcement Officials in Land Disputes Resolution Through General Court in Indonesia - Rielly Lontoh; Ronny A. Maramis; J. Ronald Mawuntu; Abdurrahman Konoras (AIBPM Publisher, 2021)
The role of the judiciary, law enforcement officials in the resolution of disputes is important. The number of disputes is increased, many authorities in Indonesia produce multiple decisions with conflicting legal force making it difficult to execute. The purpose of the study was to find the standardization of competency of law enforcement officials, the relationship between the professionalism of law enforcement officials and legal certainty in the settlement of land disputes as mandated by Article 33 paragraph (3) of the 1945 Constitution and the Basic Agrarian Law Number 5/1960. Settlement of land disputes is achieved through the General Court and the Administrative Court. The existence of regulations regarding competency standards for law enforcement officials who handle land disputes for the sake of fair settlement of land disputes and legal certainty.